Gas Chromatography-Mass Spectrometry Identification of Changes in Odor Characteristics of Live Crassostrea gigas during Different Circulation Stages - LIN Hengzong, LIANG Zhiyuan, QIN Xiaoming, GAO Jialong, FAN Xiuping, HUANG Yanping, CHANG Xiangyang, DENG Jie, WU Weijun (Shipin Kexue, 2023)
This study aimed to reveal the flavor quality changes of live oysters during different steps of circulation, and optimize the management of live oyster transportation in order to improve the survival quality of oysters. The changes in the types and contents of volatile flavor compounds in Crassostrea gigas sequentially subjected to depuration, induced dormancy and simulated waterless live transportation were investigated using solid phase microextraction coupled to gas chromatography-mass spectrometry (SPME-GC-MS). Results showed that a total of 49 volatile flavor substances were identified in live C. gigas, including aldehydes, ketones, esters, hydrocarbons, alcohols, nitrogen-containing and sulfur-containing heterocyclic compounds. Post-harvest stress had a significant impact on the flavor quality. The content of pleasant flavor compounds was significantly enhanced while the content of irritating odor substances was evidently reduced, and lipid oxidation was significantly alleviated after 24 h of depuration. Lipid oxidation in oysters was increased with waterless live transportation time, and the total amount of volatile flavor substances was slowly accumulated. Odor activity values (OAVs) showed that heptanal, nonanal, (E)-2-nonenal, 4-ethylbenzaldehyde, hexanal, (E)-2-octenal, undecanal, (E)-2-decenal, decanal, (E,E)-2,4-nonadienal and 2-pentyl furan were the key flavor substances of live C. gigas, which could be used as a reference to reflect the physiological status of live oysters. Principal component analysis (PCA) showed that the cumulative contribution of the first three principal components to total variances was 85.6%, allowing a clear distinction between the different stages of circulation. In conclusion, the vitality and flavor substances of C. gigas reach a new level after post-harvest depuration for 24 h, which is more conducive to long-term low temperature and waterless live oyster preservation. Meanwhile, the analysis of volatile components can be used as a method to identify the vitality during the circulation of live shellfish.